2021
DOI: 10.48084/etasr.4280
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Performance of a Microstrip Antenna by Adding a Slot into Different Patch Designs

Abstract: Microstrip patch antennas are attractive for communication applications due to their small size, low cost, and easy fabrication. Regardless of the diverse usage of these antennas, their bandwidth and efficiency are still limited and need to be improved. Therefore, this paper aims to enhance the bandwidth and efficiency of a microstrip antenna by inserting a slot into various patch designs. Flame Retardant (FR4) material is used in the dielectric substrate and the antenna is fed by a microstrip line. Virtually,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…This gain and bandwidth test requires a dipole antenna as a transmitter. The dipole antenna is the choice as a transmitter because the dipole antenna is close to a perfect antenna, which is an isotropic antenna [14].…”
Section: E Gain and Bandwidth Testing Resultsmentioning
confidence: 99%
“…This gain and bandwidth test requires a dipole antenna as a transmitter. The dipole antenna is the choice as a transmitter because the dipole antenna is close to a perfect antenna, which is an isotropic antenna [14].…”
Section: E Gain and Bandwidth Testing Resultsmentioning
confidence: 99%
“…E Sandi et al [63] implemented the slot technique for the improvement of bandwidth and introduced an air gap between two substrate layers, which improved the gain for millimetre wave frequencies. In addition to slots at the planar structure of the antenna, slots are created in the ground layer which is located at the front and backside of which improves the return loss [64]. Beyond using of single slot method, two slots are made [65] and it is observed to produce the tree different resonating frequency of operation with improved return loss parameter.…”
Section: U-slotsmentioning
confidence: 99%
“…Many studies have been conducted to improve the radiation characteristics of microstrip patch antennas for 5G systems. A major drawback of microstrip antennas is their narrow bandwidth, which can be increased by slotted patches, thick substrates, low effective permittivity substrates, multiple resonance integration, and impedance matching optimization [16][17][18]. In addition, the use of mmWaves has some issues related to high path loss, atmospheric and rain absorption susceptibility, and shadowing by materials as well as the human body, which can all be overcome by employing antennas that exhibit high gain and wide bandwidth [19].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies focused on using microstrip patch arrays to enhance beamforming and directivity, hence the gain of microstrip patch antennas for 5G applications [13,15,17,[30][31][32][33][34][35][36][37][38][39][40][41][42]. These studies showed that some array structures resulted in gains that exceeded 10 dBi.…”
Section: Introductionmentioning
confidence: 99%